Characterization of Seasonal Difference of HULIS-C Sources from Water Soluble PM2.5 in Seoul, Korea: Probing Secondary Processes - Hyung-Min Lee; Se Pyo Lee; Yugen Li; Jian Zhen Yu; Jin Young Kim; Yong Pyo Kim; Ji Yi Lee (Aerosol and Air Quality Research)
Abstract HUmic-LIke Substances (HULIS) consists of a significant fraction of water-soluble organic carbon (WSOC) and optically active brown carbon. Understanding seasonality in their abundance and sources is an important step to quantifying their impacts on air quality and climate. In this study, we characterized the seasonal variation of HULIS-C (the carbon component of HULIS) and identified primary and secondary sources contributing to HULIS-C at an urban site in Seoul, Korea by analyzing 131 PM2.5 samples collected over a year from October 2012 to September 2013. The HULIS-C in Seoul had an annual average of 2.0 µg m−3, and displayed a seasonality of highest abundance in the winter (2.7 ± 1.3 µg m−3) and the lowest in the summer (1.7 ± 0.8 µg m−3). Its fraction in WSOC reached up to 0.96 in the summer while remained relatively constant in the range of 0.4–0.6 in other seasons. Sources of HULIS-C were resolved using Positive Matrix Factorization (PMF) and checked using inter-species relationships between HILIS-C and aerosol components. Specifically, secondary processes including aging and heterogeneous reaction (26%) contributes to the year-round background concentration of HULIS-C and fresh biomass burning (38%) and incomplete combustion (16%) were the major sources of underlying seasonal variation. We also found aging process in the secondary process had an important role in HULIS-C formation and was a dominant contributor in the summer while heterogenous reaction contributed considerably in other seasons. It implies that the different secondary processes in forming HULIS should be considered when the radiative forcing of brown carbon is estimated. Because these processes can lead the different physicochemical properties of HULIS in aerosols.